The significant roles of internet centre (information providers) to rural community in Malaysia / Marhaini Mohd Noor and Abdul Raufu Ambali - Mohd Noor, Marhaini; Ambali, Abdul Raufu (Faculty of Administrative Science and Policy Studies, 2014)
This paper focuses on community informatics (CI) and how it is best applied to the Rural Internet Centre (RIC) programs to bring about beneficial outcomes to rural communities as a whole. For instance, it is difficult for rural communities to bridge the gap between urban and rural communities as a result of this digital inequality. Therefore the telecentre located in rural areas face challenges to sustainability. Methodologically, online survey and semistructured interviews were conducted in this research project to establish multi-stakeholders’ different views of the effectiveness of CI in RIC program in achieving its aims and outcomes. The results of statistical and narrative analysis of the quantitative and qualitative data are presented and discussed. The findings show that the rural communities are aware of social networking and accept it through the RIC programs. They are willing to learn and improve their knowledge and skills in Information and Communication Technology (ICT) from accessible training courses and workshops. Theoretically, this research has shown that the RIC improved the individual community QoRL with the use of ICT applications and services. Our study reveals effectiveness and acceptability of CI programs in regional and rural Malaysia, and suggests possible further improvements through implementing appropriate public policy programs.